Annual concentrations of polycyclic aromatic hydrocarbons (PAHs) in the North West Indo-Gangetic Plain (NWIGP) - Chandra Boggarapu Praphulla; Durga Prasad Patnana; Pooja Chaudhary; Baerbel Sinha; Vinayak Sinha (PANGAEA, 2024)
Measurements of daily average concentrations of 7 PAHs (benzo[a]anthracene (B[a]A), benzo[b]fluorenthene (B[b]F), benzo[k]fluorenthene (B[k]F), benzo[a]pyrene (B[a]P), dibenzo[ah]anthracene (D[ah]A), benzo[ghi]perylene (B[ghi]P), and indeno[1,2,3-cd]pyrene (IND)) are reported from a regionally representative sub-urban site in the North West Indo-Gangetic Plain (NWIGP). Samples were collected on prebaked quartz filters (Pall TissuquartzTM filters, 2500 QAT-UP, 47 mm diameter, 2 μm pore size) at a flow rate of 6.7 L min-1 for 24 hours (10:00 AM to following day 10: 00AM, IST) using the Speciation Aerosol Sampling System (SASS, Met One Instruments Inc., OR, USA) installed on the rooftop (80 feet above ground level) of the Academic Building-2 (30.667°N, 76.729°E), Indian Institute of Science Education and Research, Mohali, India. A total of 31 samples were collected between 13 April 2019 to 25 February 2020. After the sample collection, quartz filters were placed in aluminum foil layered petri slides, sealed with parafilm and stored at 4°C prior to chemical analysis with LC-ESI-MS/MS (Liquid Chromatography – Electrospray Ionization – Tandem Mass Spectrometer) housed at Central Research Instruments Facility (14.1670°N, 77.8091°E) at Sri Sathya Sai Institute of Higher Learning (SSSIHL), Puttaparthi, Andhra Pradesh, India.